Identifications of Wavelenght, Absorbance and Reflectance of Robusta Coffee During the Postharvest Process - Nur Ismi Syarifuddin; Olly Sanny Hutabarat; Daniel Useng; Febriana Intan Permata Hati (Salaga Journal, 2023)
Spectrometer is one of the tools that can produce a spectrum of light with certain wavelengths. A wavelength produced by measurements using a spectrometer will produce absorbance, reflectance and transmittance values. The result of light absorbed by the object is called absorbance, the light reflected by the object is called reflectance, while that which is not absorbed and not reflected by the object is called transmittance.Objective. The purpose of this study are the wavelength, absorbance value, reflectance and its relationship to color in the post-harvest process so that it is expected to be a reference and can provide information about wavelength, absorbance value, reflectance and its relationship to color in the post-harvest process.Methods. Measuring wavelenght, absorbance and reflectanceduring the postharvest process, both before treatment and after treatment. Results. The results obtained are the absorbance value of fresh green coffee of 0.98%, fresh yellow coffee of 0.18% and red coffee of 0.27%. However, after going through the post-harvest process there is a change in the absorbance value where green coffee that has been dried using the yellow honey method has decreased by 0.92% and the black honey method is 0.38% while yellow and red coffee beans have increased at wavelengths ranging from 300-400 nm and 400-500 nm, as well as roasted coffee. While the reflectance value can be seen that fresh green coffee has a reflectance value of 92%, yellow coffee is 89% and red is 69%. However, after going through the post-harvest process where green and yellow coffee that has been dried using the black honey and yellow honey methods has decreased and red coffee beans have increased at wavelengths around 900-1000 nm, as well as roasted coffee, therefore, can be concluded that the post-harvest process causes the absorbance and reflectance values to change at the same wavelength.These findings are expected could provide the information regarding the change of wavelength, absorbance and reflectance during coffee processing.